Políticas de educação e regulação de capital cultural - Sampaio, Edna Luzia Almeida (2011)
The present study deals with two basic questions: The State as organizer of the competition for different capitals in a certain society and the organization of the institutional field in the implementation of education politics, having for organizational structure the federalism. For an analysis of these convergent dimensions (State, federalism and institutional field in the scope of the education), it is taken as case study the Politics of Formation of Professors, from the concrete reality of the State of Mato Grosso and the cities of Cuiabá and Cáceres. What it intents is to understand how interlaced the federative arrangement of patrimonial trace and the pertaining to school system, in view of its regulating function in the cultural stock market. As conducting wire of the case study the politics of formation of professors was selected. The federalism while model of administrative political organization of the State, whose principles if base on the United States model, composes the problematization of the reality politics in question. The education politics reflect this model that legitimizes as univocal form to think the State, strengthening the dispersion of the politics and, at the same time, promoting the reinforcement of the local power. The spite of this, the principle of autonomy of the federate beings is submerged by the abyssal inequality that misrepresent the concepts of State and Cities as entities equivalents with severe effect on the capacity of government of each being and on the access the different types of capitals, in special the cultural capital